Potensi Wakaf sebagai Islamic Social Finance dalam Pemulihan Ekonomi Indonesia Pasca Pandemi Covid-19 - Faradila, Alfya; Ramadani, Awalia; Tunggadewi S, Fortuna; Aulia R, Nada (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2022)
The pandemic that has occurred since 2020 has increase unemployment as well as micro, small and medium enterprises (MSMEs) which have suffered losses and exit from the market. These cause unstability condition of the Indonesian economy. Alternative solution that can be explored is Islamic Social Finance, one of which is waqf. Unfortunately, the huge potential of waqf is not followed by the realization which is so lomited. Therefore, many ways are needed to realise the potential of waqf. One that can be applied is to increase the use of cash waqf which can be channeled into qardhul hasan loan capital for people in need and another way, namely Cash Waqf Linked Sukuk. This study uses a descriptive qualitative approach and library research techniques, where the data is obtained from various literatures in the form of journals, articles, survey reports, and the results of previous research. By using the AD-AS curve analysis, if waqf is used as an Islamic social finance instrument as an economic recovery and its management runs optimally, they will be able to increase aggregate demand and aggregate supply so it will have a positive effect on the country's economic growth.